Metagenomic analysis revealing links between age, gut microbiota and bone loss in Chinese adults - Yufeng Li; Zhun Shi; Xiuying Zhang; Huahui Ren; Hongyi Ji; Fangming Yang; Zuodi Fu; Xiangshuang Kong; Xiaoguang Cheng; Junhua Li; Kui Wu; Yiyi Zhong; et al. (npj Metabolic Health and Disease)
Abstract Accumulating evidence has linked gut microbiota to bone health. However, investigations into the impacts of aging, gut microbiota, and their interactions in the development of osteoporosis remain inconclusive. We employed quantitative computed tomography to measure lumbar bone mass density (BMD) and analyzed shotgun metagenomic data in 684 Chinese adults. Our analyses revealed significant positive associations between BMD and abundances of multiple Lachnospiraceae species, including Lachnospira eligens, Blautia wexlerae, and Roseburia hominis, as well as pathways involved in L-arginine biosynthesis and butyrate production—independent of age, diet habits, and lifestyles. Moreover, we demonstrated that individuals with enterotype Bacteroides exhibited a more pronounced age-related decline in BMD compared to those with enterotype Prevotella, a pattern we validated in an independent cohort. Our findings offer valuable insights into BMD-related gut microbial features and interactions between aging, gut microbiota, and bone loss, opening potential avenues for microbiota-based prevention and treatment strategies for osteoporosis.